Perlindungan Hak Asasi Manusia: Analisis Perkembangan Perlindungan Hak Asasi Manusia Di Indonesia - Fawaid Fawaid; Mohammad Haris Taufiqur Rahman; Dian Puspita Sari (International Forum of Researchers and Lecturers, 2023)
Human rights are basic rights or citizenship that are inherent in individuals from the moment they are born by nature, which are given directly by God Almighty, whose existence cannot be taken away or revoked and must be respected, upheld and protected by the state, law, government and every person. for the sake of honor and protection of human dignity. Indonesia is a country based on law. So the Indonesian state is obliged to provide human rights protection to every citizen. Meanwhile, a legal state is a state based on legal sovereignty. The law is sovereign. The state is a legal subject, in the sense of rechtstaat. Because the state is seen as a legal subject, if it is guilty it can be prosecuted before a court for violating the law.